Introduction of Gear Data Exchange Format Standard of German - Guo Xiaozhong; Shi Zhaoyao (Jixie chuandong, 2018)
The German Gears Data Exchange Format（ GDE） standard is one of the concrete practices of the German Industry 4. 0. In the GDE,the gear geometry,modification information,tolerance information,gear manufacturing tool information are defined and stored as XML（ Extensible Markup Language） documents,and supports user defining their custom information. The unified management of gear information by computer and can be quickly and accurately and stably exchanged in computer or network system is realized by GDE. It provides the technical basis of modern manufacturing informatization. It is widely used to control in the process chain,compare the measurement results and purchase tools in the major gear-related enterprises around Germany which achieved good results. It is of great reference to China gear industry towards Made in China 2025.